ROLE OF NURSES IN PROMOTING PHYSICAL ACTIVITY AND NUTRITION - Altayawi, Nawaf Judaya F, Najwan Fraih Alanazi, Helah Fraih Alanazi, Alanoud Fayadh Alruwaili, Fareed Muadhid Munahi Alotaibi, Yousef Fahad Monahi Alotaibi, Azza Ahmed Hamed Alghamdi, Nawal Mohsen Altheyabi, ,; Fadia Ali Aishi, Sattam Majed, Almutairi, Amani Mazyad Almutairi, Lolo Saleh Alhamed, Tahani Ayed Al-otaibi, (Chelonian Research Foundation, 2022)
Prior studies have explored many approaches to enhance the health, wellness, and job-related results of nurses. Nevertheless, the extent of this evidence remains ambiguous, and the specific interventions that are most likely to provide favorable results are still unclear. Purpose: To provide a comprehensive analysis and amalgamation of the efficacy of treatments used to enhance the health, well-being, and job-related results for nurses. Most of the therapies prioritized education, physical exercise, mindfulness, or relaxation. Twenty-seven percent of the studies used a multimodal therapeutic method. The overall results were inconclusive, as several research reported positive outcomes while others saw no discernible impact. The outcome that showed the highest success rate of change (8 out of 9) was dietary habits. This was followed by body composition indices (20 out of 24), physical activity (PA) (11 out of 14), and stress (49 out of 66). In each of these categories, over 70% of the relevant studies reported improvements. The work-related outcomes had the lowest success rate, with 16 out of 32 cases being successful. Individual analysis of randomized controlled trials (RCTs) suggests that treatments that only prioritize education may have a lower likelihood of producing beneficial results compared to therapies that specifically target behavioral change. Interventions that focus on food, body composition, physical activity, or stress management are the most likely to have favorable results for the health and wellbeing of nurses. The most rigorous data, based on randomized controlled trials (RCTs), is available for the assessment of body composition and stress. Interventions that only depend on instructional methods are the least certain to be successful. Modifying organizational results via lifestyle intervention seems to be a more difficult task, necessitating more intricate solutions that include altering the work environment. Additional high-quality evidence is required due to the prevalence of studies with moderate or high risk of bias and poor reporting quality. Keywords: lifestyle intervention; systematic review; nurses; employee wellness; workplace intervention